Infancias, subjetividades y cibercultura: noopolítica y experiencia de sí - JUAN CARLOS AMADOR (Revista Científica, 2012)
his paper presents the research results about subjectivities and subjecti- vity forms that are produced in the context of the uses and appropriations of a children Bogotá group. It was developed in the social networking site Facebook, as part strategic cyberculture. The first part presents the subject matter and the scope of the research exercise. In the second part are some approaches to concepts and theoretical framework of the problem and deepen the discussions on the childhoods - media-technologies and sub- jectivities. In the third part presents the methodological considerations. At the end shows the appropriations.